Análisis de factibilidad de un sistema de generación fotovoltaica para el sector residencial de la ciudad de Loja. - Rivas Celi, Edgar Rafael (2015)
This research is about the feasibility of using of photovoltaic panels in the residential sector in Loja city as a clean energy alternative, due to solar potential and geographical location. I proceeded to establish the energy demand of a typical home with the most useful electrical appliances to find out the electrical power to solve by the photovoltaic system. The system is versatile for the user so, he may use the electrical system provided by Empresa Eléctrica Regional del Sur S.A (EERSSA) or the photovoltaic system. Another thing that I get from the Methereologyc Station “La Argelia” was the information of the sun radiation on the city, which has been monitoring this since March, 2013. Then I choose the method “worst month” because this is the most used method to dimensioning this kind of system, as well as all the equipment that will be used in the photovoltaic system for the house type, and the angles attached to the panels and wiring fixed. Finally we did the technical-economic analysis of all equipment and materials that will be used to determine the feasibility of the system.